Selecting the most effective alternative of waterproofing membranes for multifunctional inverted flat roofs - Kalibatas, Darius; Kovaitis, Vytautas (Journal of Civil Engineering and Management, 2017)
There are many various methods, techniques and materials for constructing multifunctional inverted flat roofs now. However, in practice, the constructed roofs of this type often have various defects, whose elimination is rather costly. To solve this problem, the analysis of multifunctional inverted flat roofs has been performed and their advantages and disadvantages, as well as building defects and mistakes made in the course of construction, have been demonstrated. Damp-proofing materials available on the market for making waterproofing membranes for multifunctional inverted flat roofs have been evaluated. The problem of choosing the most effective membrane alternative for the investigated type of roofs is solved by analysing ten alternatives with the help of multi-criteria evaluation method, SAW and three game theory rules determined by Hurwicz, Laplace and Bayes, as well as LEVI 3.0 program. The analysis of the results has shown that the alternative No. 5 is the best membrane alternative among the ten considered options.First published online: 03 Apr 2017